2021
DOI: 10.3390/toxins13020093
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of the Toxin Domoic Acid in Antarctic Diatom Species

Abstract: The Southern Ocean is one of the most productive ecosystems in the world. It is an area heavily dependent on marine primary production and serving as a feeding ground for numerous seabirds and marine mammals. Therefore, the phytoplankton composition and presence of toxic species are of crucial importance. Fifteen monoclonal strains of Pseudo-nitzschia subcurvata, a diatom species endemic to the Southern Ocean, were established, which were characterized by morphological and molecular data and then analysed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Hence, we collected samples for DA (dissolved and particulate forms) measurements as described in Geuer et al (2020). In contrast to the study by Olesen et al (2021), which reported the presence of DA in several P. subcurvata strains, no DA was extracted from the cells and the culture medium of all our treatments, indicating that our P. subcurvata strain was unable to produce DA (data not shown).…”
Section: Methodscontrasting
confidence: 99%
“…Hence, we collected samples for DA (dissolved and particulate forms) measurements as described in Geuer et al (2020). In contrast to the study by Olesen et al (2021), which reported the presence of DA in several P. subcurvata strains, no DA was extracted from the cells and the culture medium of all our treatments, indicating that our P. subcurvata strain was unable to produce DA (data not shown).…”
Section: Methodscontrasting
confidence: 99%
“…Domoic acid is the primary ASP-causing toxin, with multiple studies assessing DA production by Pseudo-nitzschia . In contrast, there are only a few studies which assess DA isomer production by Pseudo-nitzschia strains: iso-DAs A and B from P. delicatissima , P. multiseries [ 48 ], and P seudo-nitzschia seriata [ 49 ], iso-DA C from P. australis [ 50 , 51 ] and P. subcurvata [ 52 ], and epi-DA and iso-DAs A and D from P. plurisecta [ 53 ]. This is the first study to screen, and report, iso-DA E production by Pseudo-nitzschia strains.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from DA, the present study detected all, or a combination of, the tested DA isomers (epi-DA and iso-DA A–E) from all P. australis and P. multiseries strains analysed. Recently, Olesen et al (2021) [ 52 ] reported relative amounts of DA and iso-DA C in three P. subcurvata strains. The authors reported that the proportion of DA tended to be lower than that of iso-DA C (DA:iso-DA C = 34–49%:51–66%) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations